AN ANALYSIS ON THE ENGLISH TEACHER’S STRATEGIES IN TEACHING READING COMPREHENSION AT THE SECOND GRADE STUDENTS OF JUNIOR HIGH SCHOOL 12 OF MATARAM - Suryaningrat, Susan; Syahrial, Edy (Jurnal Ilmiah Pendidikan Indonesia, 2021)
This research is aimed at finding out the types of the strategies mostly used by the teachers in teaching and the effect of the strategies used in teaching English Reading Comprehension on students reading skill (recount text). The subjects of this study were the English teacher and eighth grade students of SMP 12 Mataram in the academic year of 2019/2020. The data was analyzed qualitatively. The findings showed that the strategies mostly used by the teachers were three strategies. Those were; discussion, question and answer and interview. While the effect of the strategies used in teaching English reading (recount text) make students more active, interested, enjoy, and enthusiastic in following the learning process. This can also be seen from the increasing student learning outcomes.